The Role of Movement and Song Methods on the Development of Gross Motor Skills in Children at TK Negeri 2 Tanah Pinoh - Umi Kalsum; M. Akip (Educia Journal, 2026)
Gross motor development is a fundamental aspect of early childhood development that supports children's physical, cognitive, social, and emotional growth. However, opportunities for structured physical movement in early childhood education settings are often limited, resulting in insufficient stimulation of children's gross motor skills. This study aimed to analyze the role of the movement and song method in the development of gross motor skills among children at TK Negeri 2 Tanah Pinoh, Melawi Regency, West Kalimantan. The study employed a descriptive qualitative approach involving classroom teachers and Group B children as research participants. Data were collected through observations, interviews, and documentation and were analyzed using the interactive model of data analysis, including data condensation, data display, and conclusion drawing. The findings revealed that the movement and song method contributed significantly to the development of children's locomotor, non-locomotor, and manipulative skills. Through activities involving coordinated body movements and rhythmic songs, children demonstrated improved balance, coordination, agility, and body control. In addition, the method increased children's participation, enthusiasm, concentration, and confidence during learning activities. The findings further indicate that movement and song activities create a holistic learning environment that simultaneously supports physical, emotional, and social development. The study concludes that the movement and song method is an effective and developmentally appropriate pedagogical strategy for enhancing gross motor development in early childhood education. Therefore, integrating movement-based learning activities into daily classroom instruction is recommended to promote active learning and support children's overall developmental outcomes.